2019
DOI: 10.14814/phy2.14202
|View full text |Cite
|
Sign up to set email alerts
|

Exercise alters the molecular pathways of insulin signaling and lipid handling in maternal tissues of obese pregnant mice

Abstract: Obesity during gestation adversely affects maternal and infant health both during pregnancy and for long afterwards. However, recent work suggests that a period of maternal exercise during pregnancy can improve metabolic health of the obese mother and her offspring. This study aimed to identify the physiological and molecular impact of exercise on the obese mother during pregnancy that may lead to improved metabolic outcomes. To achieve this, a 20‐min treadmill exercise intervention was performed 5 days a week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Intake of a diet high in both sugar and fat (HSHF) during pregnancy also impacts maternal β-cell adaptations, but the specific effect depends on the diet composition and dietary protocol used. Nevertheless, pregnant mice fed a HSHF diet show increased adiposity in association with an altered lipid profile, increased levels of leptin and defects in tissue insulin sensitivity (Holemans et al 2004;Sferruzzi-Perri et al 2013;Fernandez-Twinn et al 2017;Musial et al 2017Musial et al , 2019J Physiol 600.5 Martins Terra et al 2019). In addition, a HSHF diet during gestation induces hyperinsulinaemia, hyperglycaemia and glucose intolerance in the mother (Sferruzzi-Perri et al 2013;Fernandez-Twinn et al 2017;Musial et al 2017;Martins Terra et al 2019).…”
Section: Maternal Diet or Nutritional Statusmentioning
confidence: 99%
“…Intake of a diet high in both sugar and fat (HSHF) during pregnancy also impacts maternal β-cell adaptations, but the specific effect depends on the diet composition and dietary protocol used. Nevertheless, pregnant mice fed a HSHF diet show increased adiposity in association with an altered lipid profile, increased levels of leptin and defects in tissue insulin sensitivity (Holemans et al 2004;Sferruzzi-Perri et al 2013;Fernandez-Twinn et al 2017;Musial et al 2017Musial et al , 2019J Physiol 600.5 Martins Terra et al 2019). In addition, a HSHF diet during gestation induces hyperinsulinaemia, hyperglycaemia and glucose intolerance in the mother (Sferruzzi-Perri et al 2013;Fernandez-Twinn et al 2017;Musial et al 2017;Martins Terra et al 2019).…”
Section: Maternal Diet or Nutritional Statusmentioning
confidence: 99%
“…Overall, animal studies have shown that exercise improves insulin sensitivity, lipid metabolism and glucose tolerance in diabetic and obese rodent pregnancies [ 33 ]. A study by Musial et al [ 34 ] used a mouse model and aimed to determine the effects of obesity during pregnancy with and without an exercise intervention on maternal body weight and composition, nutrient handling, and insulin and lipid signalling in liver, skeletal muscle, and adipose tissue. It was found that exercise induced changes in the insulin and lipid signalling pathways in obese dams that differed from those observed in control and sedentary‐obese dams.…”
Section: The Benefits Of Lifestyle Interventions On Mother and Child In The Context Of Weight Development And Gdmmentioning
confidence: 99%
“…A similar study also investigated possible biochemical mechanisms that could explain the observed protective effects of exercise on obese, maternal mice during gestation ( 147 ). Control maternal mice were on a CD and remaining maternal mice were fed an obesogenic diet and divided into sedentary and exercise groups.…”
Section: Exercise Studies In Animal Modelsmentioning
confidence: 99%